SISTEM PENJAMINAN MUTU DAN PENGAWASAN PENDIDIKAN TINGGI - Alwan Suban (al-fikrah: Jurnal Manajemen Pendidikan, 2021)
This study aims to determine the internal quality assurance system for education standards, research, community service and educational supervision in higher education institutions. The results of the study indicate that all components of the education quality standard must be endeavored to achieve the desired quality, both internal and external stakeholders. Research standards and community service need to be intensified in carrying out an internal quality assurance system by referring to the principles of being educational, accountable, objective, and transparent. Educational supervision in tertiary institutions must always be present to complement the administrative and management processes in achieving educational goals and become an umbrella for inputs, outputs and systems in tertiary institutions to keep activities carried out from deviating from a predetermined plan.